Effect of Meditation On Self-Control of Mind: Life Sciences- Ayurveda - R. Bhagat, Dr. Kavita; R. Kale, Dr. Deepa; Gupta, Dr. Rajkumar; Menon, Dr. Sudeep (International Journal of Life Science and Pharma Research, 2023)
Anxiety neurosis is common due to today’s lifestyle challenges. People often cannot handle their emotions and getangry, depressed, and anxious. Meditation Helps to eliminate negative emotions and develop positive emotions, increaseconcentration, enhance memory, give clarity of thoughts, and improve willpower. The current research work discusses the Karmasof Manasa such as Indriyabhigraha and Swasyanigraha (self-control), the Sattvavajaya Chikitsa, anxiety neurosis as a result of abnormalSwasya Nigraha, the utility of meditation for control on self, i.e., Swasyanigraha. The present study was carried out to study theself-control function of the mind and the effect of Twin Heart Meditation in anxiety neurosis subjects. In the present single-armstudy, 114 young adults (aged 18-35 years) with diagnosed anxiety neurosis based on Ayurvedic Sattva Parikshana criteria and theHamilton anxiety rating scale were selected. They were prescribed Meditation or Dhyana for 90 days. Follow-up was taken every30 days to assess anxiety symptoms according to the Hamilton anxiety rating scale. All the 114 participants showed improvement.Moderate improvement was observed in most of the participants. (91%) Based on the results of the present study done throughthe Hamilton Anxiety Rating Scale and Ayurvedic Satva Parikshana Scale, it can be inferred that the Twin–Hearts Meditation forconsecutive 90 days in individuals suffering from mild to moderate anxiety neurosis enhances Swasyanigraha Karma (Self Control).